2021
DOI: 10.1093/eurheartj/ehab151
|View full text |Cite
|
Sign up to set email alerts
|

Sleep arousal burden is associated with long-term all-cause and cardiovascular mortality in 8001 community-dwelling older men and women

Abstract: Aims  To quantify the arousal burden (AB) across large cohort studies and determine its association with long-term cardiovascular (CV) and overall mortality in men and women. Methods and results  We measured the AB on overnight polysomnograms of 2782 men in the Osteoporotic Fractures in Men Study (MrOS) Sleep study, 424 women in the Study of Osteoporotic Fractures (SOF) and 2221 men and 2574 women in the Sleep Heart Health St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 29 publications
0
32
0
6
Order By: Relevance
“…With the surge of social pressure, more people choose to sacrifice sleep time to study, work and so on. This causes a series of health crises, such as cognitive impairment (Leng et al, 2017) and cardiovascular damage (Shahrbabaki et al, 2021). Researchers recently analyzed 25 years of health data from nearly 8,000 middleaged people and found a link between sleep and dementia as people get older.…”
Section: Introductionmentioning
confidence: 99%
“…With the surge of social pressure, more people choose to sacrifice sleep time to study, work and so on. This causes a series of health crises, such as cognitive impairment (Leng et al, 2017) and cardiovascular damage (Shahrbabaki et al, 2021). Researchers recently analyzed 25 years of health data from nearly 8,000 middleaged people and found a link between sleep and dementia as people get older.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study also supports the idea of a sex-specific impact of suboptimal sleep in CVD, finding that disrupted sleep may have a more significant impact on CVD mortality risk in women than men. 22 . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also supports the idea of a sex-specific impact of suboptimal sleep in CVD, finding that disrupted sleep may have a more significant impact on CVD mortality risk in women than men. 22…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between sleep patterns and cardiovascular health is relevant from the public health perspective since cardiovascular diseases represent a leading cause of death. Large cohort studies have shown that sleep problems, e.g., short or long sleep duration, sleep arousal, insomnia, are associated with cardiovascular diseases onset and cardiovascular mortality [4,5]. Furthermore, it has been shown that patients with cardiovascular diseases are more likely to present with sleep problems, which are, in turn, associated with a poor prognosis [6].…”
Section: Introductionmentioning
confidence: 99%